Development Evaluation and Optimization of Deep Shale Gas Reservoir with Horizontal Wells Based on Production Data. (31st August 2021) - Li, Wuguang; Yue, Hong; Sun, Yongpeng; Guo, Yu; Wu, Tianpeng; Zhang, Nanqiao; Chen, Yue
Abstract : The implementation of horizontal wells is a key to economic development of the deep shale gas reservoir. In order to optimize the key parameters for drilling, stimulation, and the production system, the development effect of a horizontal well in deep shale gas formations was investigated from various aspects in this study. The drilling, fracturing, and production performances of this well were analyzed combining with the geological characteristics. The main technical problems and key factors that restrict the gas well performance and estimated ultimate recovery (EUR) were clarified. Through the integrated study of geology and engineering, the optimization strategies for increasing gas production and EUR are provided. The Z2 area, where the Z2-H1 well is located, has good reservoir physical properties, which bring a high drilling efficiency. However, there are still some problems during its development, such as poor fracture extension both horizontally and vertically, limited stimulated reservoir volume (SRV), rapid production declining, large water production, and serious liquid accumulation. In this study, a comprehensive approach was proposed that can improve single-well production and EUR by optimizing the target position, horizontal section length, pathway, spacing, new drilling and fracturing technology, and production system.